British entrepreneurship in the nineteenth century - Payne, Peter Lester (Macmillan, 1974)
The quality of British enterpreneurship in the nineteenth century is being reassessed. Until recently a major leitmotiv in accounts of British economic development from the heroic days of the Industrial Revolution to eve of the First World War has been the steady dissipation of a fund of entrepreneurship which, it has been implied, reached its greatest abundance during and immediately after the Napoleonic Wars